IMPLEMENTASI KESEJAHTERAAN SOSIAL BAGI PENYANDANG MASALAH LANJUT USIA PERSPEKTIF MAQASHID SYARI’AH DI KOTA MALANG - F.T. Mu’alim; M. Djakfar; A.S. Supriyanto (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Introduction: Malang City is committed to be an Elderly Friendly City. A number of policy innovations and pro social welfare programs for the elderly have been implemented. But in fact the aid is still in the form of material such as money and basic necessities. The varied conditions of the elderly require the fulfillment of non-material needs such as health, moral support and religious development. To understand the implementation of welfare for people with elderly problems in Malang City, the maqashid shari'ah perspective is used so that the factual needs of the elderly can be understood more comprehensively. Methods: The research method used is a qualitative paradigm with the type of case study research. The data analysis technique uses data reduction, presentation, conclusion and verification. Results and Conclusion: The results of the study indicate that the social welfare program is tentative and continuous. The tentative program is material, while the continuous program is non-material. The implementation of the program is carried out by the Social Service in collaboration with TKSK, PSM and local village officials. The stages in program implementation are receiving reports, visitation by providing an analysis of environmental potential and ending with evacuation if needed. Maqashid shari'ah corrects that social welfare programs have implications but have not maximized maintaining religion, soul, mind, lineage and property, especially during the Covid-19 pandemic. The implication for the unproductive elderly comes from non-material assistance such as assistance and love. Meanwhile, material assistance has implications for productive elderly people for business empowerment. Key words: Implementation of Social Welfare, Elderly Problems, Maqashid Syari'ah.